GEGURITAN SRI SEDANA ANALISIS STRUKTUR DAN FUNGSI - Sulyanthini, Luh Putu (Humanis, 2014)
This research looked into Bali belleslettres Tradisional that organized as geguritan with title "Geguritan Sri Sedana". In geguritan occurred ten type canto in 35 stanza. Purpose from this research namely to know structure forma and structure narrative as well as functions that are developed geguritan In this research used structural theory and theory function that is combination from opinion all man of letters. Method and technique used divided become three stage, namely first data supply stage by using method read with technique record and translation, second data analysis stage use qualitative method with descriptive analytical technique, and third analysis result presentation stage data use formal and informal method. Result obtained from this research is is revealed him structure form and structure narrative that build "Geguritan Sri Sedana" that include structure form: language codes and literature, locution, and language variety, as well as structure narrative: incident, groove, figure and characterization, plane, theme, and mandate. In addition to this research also couched functions that are covered: function as inner compass religious, function as inner compass behave, function as myth.
Keywords: structure, function, sri sedana